Hand grip strength vs. locomotor efficiency in sitting volleyball players - Wilinski, W.; Struzik, A.; Rokita, A.; Krejci, M.; Wieczorek, M. (Journal of Human Kinetics, 2022)
The objective of this paper was to determine the relationship between hand grip strength and movement time (locomotor efficiency in a seated position using the upper and lower extremities) in sitting volleyball players. In addition, a comparison was made between the velocity curves for forward and backward locomotion. Nine male members of the sitting volleyball team participated in the study. Hydraulic and spring manual dynamometers were used to measure hand grip strength. Movement times were registered for distances of 1, 2, 3, 4, 5, 6 and 10-m with the use of the Smart Speed System photocells. Significant relationships between hand grip strength of the left (rs=-0.78) and right (r s =-0.73) hands and the forward movement time over a distance of 1-m were found. Hand grip strength had no significant relationship with either forward movement times at other distances or backward movement times. Results suggest that hand strength is linked to locomotor efficiency of sitting volleyball players. High hand grip strength makes the start easier by pushing away from the ground with the upper limbs.